Analisis Strategi Ekspansi Kopiko (PT. Mayora Indah Tbk) Memasuki Pasar Internasional - Arfina Sabila; Cindy Dwiana Putri; Nadia Indah Lestari; Lenti Susana Saragih; Aurora Elise Putriku (Jurnal Bisnis Inovatif dan Digital, 2024)
This research aims to analyze Kopiko's expansion strategy in entering international markets. Kopiko, as a superior coffee candy product from Indonesia, has successfully penetrated more than 80 countries throughout the world. This research uses a qualitative approach with a literacur study method to understand the strategies implemented by Kopiko in achieving global success. Data was obtained through in-depth literature study on the official PT website. Mayora Indah Tbk, analysis of company documents, and related previous research. The research results show that Kopiko's success in the international market is supported by several key factors, namely: (1) product adaptation according to local consumer preferences in each country; (2) effective marketing strategies, including the use of social media, influencers, and engaging advertising campaigns; (3) collaboration with local distributors who have a wide distribution network; (4) continuous product innovation to maintain consumer interest; and (5) consistent product quality. Kopiko also utilizes in-depth market analysis to select target countries with high growth potential. This research concludes that product adaptation and innovation strategies, coupled with careful marketing and strategic distribution cooperation, are the main factors for Kopiko's success in international market expansion. These findings can be a reference for other companies who want to expand their business to the global market